A Note on Frames in Quaternionic Hilbert Spaces - Sumit Sharma; Raksha Sharma (Sahand Communications in Mathematical Analysis)
In this paper, we define a modified version of frame in quaternionic Hilbert spaces (QHS) and give a necessary condition for a  block Bessel sequence in terms of a bounded right linear operator. Also, a necessary and sufficient condition for a sequence to be a block Bessel sequence is given. Further, a method to construct a desired block frame using a given block frame is discussed. Finally, a characterization of block frame in terms of a right linear operator is given.